A critical examination of obstacles and opportunities to building capacity for community engaged social-ecological research and management - Hauptfeld, Kathrin "Rina" Simone, author; Newman, Gregory, advisor; Bruyere, Brett, committee member; Pejchar, Liba, committee member; Zarestky, Jill, committee member (Colorado State University. Libraries, 2024)
This dissertation seeks to contribute to more equitable and effective local governance and research of social-ecological systems. Specifically, I investigated efforts to enhance the distribution of influence and capacity, particularly to historically marginalized actors. This required critical evaluation of factors that influence whether and how interventions to build influence and capacity do so. Chapter one introduces the theoretical framing to this research, my positionality, and an overview of chapter organization. In my first two manuscripts (Chapters 2 and 3), I research underexamined elements of public participation in scientific research (i.e., delegated local ecological monitoring) as a proposed tool for building community capacity for resource management, particularly in developing economies. I seek to understand local ecological monitoring from multiple levels of influence - both the perspectives of resource-dependent participants, as well as from the perspectives of the program implementers. Specifically, Chapter 2 seeks to understand the experience of participants (i.e., small-scale fisherfolk with a role in the management of marine protected areas in the Philippines) to investigate the narrative that local ecological monitoring empowers communities to manage their social-ecological systems. I find that monitoring programs largely failed to be adopted by local communities, and rather than empowering participants, were perceived as burdens and a reaffirmation of local hierarchies. My findings highlight the risks of uncritically applying 'participatory' approaches, and stress the need to recognize and design for the psycho-political contexts (e.g., agency) to achieve desired outcomes. In considering context, this study makes a novel contribution to the characterization of citizen science approaches, by distinguishing externally initiated programs in which monitoring is intended to become autonomous. In consideration of the failed outcomes in Chapter 2, Chapter 3 investigates the potential for win-win outcomes in citizen science by examining an understudied area - organizer rationales for engaging local participants in contributory programs in the Philippines. I find that organizer rationales for and perceptions of engaging participants were multiple, overlapping, and sometimes antagonistic, particularly regarding who is served, and who determines the objectives, suggesting that outcomes often framed as benefits in the literature may sometimes not benefit participants. To foster clarity and encourage reflexivity in citizen science programs, I map these findings onto the normative – substantive - instrumental typology of rationales to propose an adapted typology rooted in the realities of citizen science. Chapter 4 addresses the flip side of the participation equation by investigating how high- 'cost' community-oriented collaborative conservation practices are built and sustained among U.S. academics and practitioners. This retrospective program evaluation found that immersion into a community of practice, and obligations and opportunities to experiment with collaborative approaches fostered capacity - notably conviction for, awareness of, and comfort with collaborative conservation - resulting in long-term adoption of practice. The findings in these studies shed light on important obstacles and opportunities for enhancing efficacy and equity in community-engaged research and management endeavors increasingly sought in social-ecological systems. Notably, a pervasive thread to emerge from these chapters is the important role of intentional design using a systems-thinking approach, regarding linked social-ecological systems, multiple levels of influence, and temporal scales.
Keywords: co-management; delegated local ecological monitoring; participation; collaborative conservation; capacity building; marine protected areas